Variably protease-sensitive prionopathy: A differential diagnostic consideration for dementia. Issue 2 (April 2019) - Kim, Stella H.; Yu, Melissa M.; Strutt, Adriana M.
Abstract : Purpose of review: Prion diseases are rare neurodegenerative diseases that are caused by abnormal pathogenic agents and can affect both humans and animals. These diseases are categorized as sporadic, inherited, or acquired by infection. Clinical manifestations include psychiatric symptoms, cognitive impairment, and parkinsonism, which are similar to those of other prion diseases and frontotemporal dementia variants. Recent findings: More recently, scientists discovered a new sporadic prion disease called variably protease-sensitive prionopathy. Summary: The following case discusses a patient presenting with sudden onset and rapid decline in cognitive, neurobehavioral, and motor functioning and his clinical journey including treatment interventions and diagnostic confirmation.